An Examination of Factors Influencing Law Enforcement in Cases of Electoral Offenses During the 2020 Regional Head Elections in Northern Lombok Regency - Taufik, Zahratul'ain; Titin Nurfatlah; Rahmadani; Baiq Vira Safitri (Magister of Law, Faculty of Law, University of Mataram, 2024)
This study aims to explore the determining factors impacting the enforcement of electoral laws during the 2020 regional elections in North Lombok Regency. Regional head elections represent a direct mechanism for the populace to elect their leaders. Given the nature of elections as a platform for power acquisition, they inherently attract transgressions, unlawful deeds, irregularities, and other violations. The Final Report of the Election Supervisory Body (Bawaslu) of North Lombok Regency revealed that while eight instances of electoral infractions were probed, only one case was prosecuted, forming the focal point of this article. The research employed normative-empirical legal research with both conceptual and case approaches, by collecting primary and secondary data, which were subsequently qualitatively analyzed. The findings indicated various factors influencing the adjudication process of electoral offenses during the 2020 Pilkada in North Lombok Regency, including disparities in the interpretation of legal statutes among law enforcement entities handling electoral crimes, inadequate evidentiary support to establish electoral infractions, and challenges in procuring testimony from cooperative witnesses.